MHCI trafficking signal‐based mRNA vaccines strengthening immune protection against RNA viruses - Yupei Zhang; Songhui Zhai; Shugang Qin; Yuting Chen; Kepan Chen; Zhiying Huang; Xing Lan; Yaoyao Luo; Guohong Li; Hao Li; Xi He; Meiwan Chen; et al. (Bioengineering & Translational Medicine)
Abstract The major histocompatibility complex class I (MHCI) trafficking signal (MITD) plays a pivotal role in enhancing the efficacy of mRNA vaccines. However, there was a lack of research investigating its efficacy in enhancing immune responses to RNA virus infections. Here, we have developed an innovative strategy for the formulation of mRNA vaccines. This approach involved the integration of MITD into the mRNA sequence encoding the virus antigen. Mechanistically, MITD‐based mRNA vaccines can strengthen immune protection by mimicking the dynamic trafficking properties of MHCI molecule and thus expand the memory specific B and T cells. The model MITD‐based mRNA vaccines encoding binding receptor‐binding domain (RBD) of SARS‐CoV‐2 were indeed found to achieve protective duration, optimal storage stability, broad efficacy, and high safety.